2011
DOI: 10.1177/0149206311416120
|View full text |Cite
|
Sign up to set email alerts
|

Investor Reactions to New Product Development Failures

Abstract: The authors develop a model of investor reactions to new product development (NPD) failures in high technology firms. They propose that a firm's financial and managerial capabilities, and its strategic focus on R&D, influence investors' perceptions of the firm's market value after NPD failure and that these effects are contingent on the development stage of the failed product. Using data on 148 NPD failures of publicly traded biopharmaceutical firms and an event study methodology the authors find support for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…New product development (NPD) is an effective measure for firms to obtain product differentiation and competitive advantages (Fang, 2008). However, as the market matures, introducing new products becomes more difficult, especially those that are novel to the market (Henard and Szymanski, 2001; Urbig et al , 2013). For example, Apple has added incremental innovations such as the high-resolved camera to new iPhones since they launched their first model in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…New product development (NPD) is an effective measure for firms to obtain product differentiation and competitive advantages (Fang, 2008). However, as the market matures, introducing new products becomes more difficult, especially those that are novel to the market (Henard and Szymanski, 2001; Urbig et al , 2013). For example, Apple has added incremental innovations such as the high-resolved camera to new iPhones since they launched their first model in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cummings and Knott (2018) found that outside CEO succession is negatively related to the firm's ability to generate sales through increased R&D investments, indicating a need for technical expertise and knowledge of internal processes to ensure the successful management of R&D investments. A single study investigates the capital market's reaction to failures in new product development and finds that managerial experience reduces negative market reactions to such failures (Urbig, Bürger, Patzelt, & Schweizer, 2013).…”
Section: An Integrative Framework On Strategic Leaders and Technologimentioning
confidence: 99%
“…Moreover, TMT education affects innovation outcomes. Science or engineering degrees (Scherer & Huh, 1992) as well as a higher level of education in the TMT (Bantel & Jackson, 1989;Heyden, Reimer, & van Doorn, 2017) With regard to the prior work experience of TMT members, when the TMT is experienced in specific topics or industries, it generally has a stronger focus on innovation activities related to those topics or industries (e.g., Hoffman & Hegarty, 1993;Somaya, Williamson, & Zhang, 2007;Urbig, Bürger, Patzelt, & Schweizer, 2013). For example, Tyler and Steensma (1998) found a positive relationship between the technical work experience of TMT members and their assessments of potential research alliances.…”
Section: Group-level Tmt Characteristicsmentioning
confidence: 99%
“…Product innovation is a process of great uncertainty and the launch of new products can have many effects on a company's competitiveness [32,33]. On one hand, revenues from new products and services can help companies to achieve profitability and market position [34], but new products with lower revenues may be abandoned if they are seen to hurt the company's competitiveness, destroy its brand image, or have a negative financial impact on investors [35]. Therefore, identifying the cause of product failure is a core challenge when managing a company's innovation activities.…”
Section: Innovation Resistance Theorymentioning
confidence: 99%